IMPLEMENTASI TEKNOLOGI INOVASI PANGAN KRIPIK KELOR SEBAGAI PRODUK UNGGULAN DESA BOBO BERKELANJUTAN - Anjelia, Ni Kadek Femi; Fahri, Fahri; Aziz, Abd; Albahar, Aulia Ramadhani; Rahmadani, Nur Fajrah; Salsabila, Anggun; Moh. Fadli, Moh. Fadli; Romadon, Mochammad Muchlis (Penerbit Widina, Widina Media Utama, 2025)
Moringa is one of the locally sourced foods rich in nutrients, but its utilization in Bobo Village is still limited, so innovation is needed to increase its added value as a village product. This service aims to introduce and encourage the implementation of innovative food technology in the form of moringa chips to the community of Bobo Village as a strategy for empowerment and local economic development. The implementation methods include initial observation to identify potential and problems, activity planning, consultation with the village government, and socialization focused on conveying information about the benefits of moringa, business opportunities, and the basic process of making moringa chips. The results of the service show that the community has a high interest in this food innovation, as evidenced by active participation during socialization and the emergence of interest in trying to produce moringa chips independently. This activity also increases public understanding of the nutritional value of moringa and the economic opportunities that can be developed thru processing local products. In conclusion, the socialization of moringa chip innovation was able to broaden the horizons of the Bobo Village community regarding the utilization of moringa as a product with economic value and the potential to become the village's flagship commodity. However, follow-up actions are needed, including technical training, production assistance, and strengthening marketing strategies, to ensure that moringa chips can be produced sustainably and have a more optimal economic impact on the community.ABSTRAKKelor merupakan salah satu sumber pangan lokal yang kaya nutrisi, namun pemanfaatannya di Desa Bobo masih terbatas sehingga diperlukan inovasi untuk meningkatkan nilai tambahnya sebagai produk desa. Pengabdian ini bertujuan untuk memperkenalkan dan mendorong implementasi teknologi inovasi pangan berupa kripik kelor pada masyarakat Desa Bobo sebagai strategi pemberdayaan dan pengembangan ekonomi lokal. Metode pelaksanaan mencakup observasi awal untuk mengidentifikasi potensi dan permasalahan, perencanaan kegiatan, musyawarah dengan pemerintah desa, serta sosialisasi yang berfokus pada penyampaian informasi mengenai manfaat kelor, peluang usaha dan proses dasar pembuatan kripik kelor. Hasil pengabdian menunjukan bahwa masyarakat memiliki ketertarikan yang tinggi terhadap inovasi pangan tersebut, ditandai dengan partisipasi aktif selama sosialisasi dan munculnya minat untuk mencoba memproduksi kripik kelor secara mandiri. Kegiatan ini juga meningkatkan pemahaman masyarakat mengenai nilai gizi kelor serta peluang ekonomi yang dapat dikembangkan melalui pengolahan produk lokal. Kesimpulannya, sosialisasi inovasi kripik kelor mampu membuka wawasan masyarakat Desa Bobo mengenai pemanfaatan kelor sebagai produk yang bernilai ekonomis dan berpotensi menjadi komunitas unggulan desa. Namun, diperlukan tindak lanjut berupa pelatihan teknis, pendampingan produksi, serta penguatan strategi pemasaran agar keripik kelor dapat dihasilkan secara berkelanjutan dan memberikan dampak ekonomi yang lebih optimal bagi masyarakat.